Unveiling the immunopharmacological mechanisms of Danggui Yinzi (DGYZ) in treating chronic urticaria: insights from network pharmacology and experimental validation - Xu-rui Wang; An-jing Chen; Chang-cheng Hou; Yue-yue Wang; Jing Guo; Ming-yue Li (Chinese Medicine)
Abstract Background Chronic urticaria (CU), a prevalent and often debilitating allergic skin disorder, is primarily triggered by mast cell degranulation. Danggui Yinzi (DGYZ), a traditional Chinese medicine formula, has been employed to treat pruritic conditions. However, the molecular mechanisms underlying its effects in CU remain unclear. This study aimed to investigate the immunopharmacological mechanisms of DGYZ in CU, hypothesizing that it modulates immune responses through its bioactive components, which is critical for the development of novel therapeutic agents. Methods Ultra-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF–MS) was used to identify the active compounds in DGYZ. In vivo, BALB/c mouse models of DNP-IgE/DNFB-induced CU were established and grouped into Normal Control (NC), Model, various-dose DGYZ, and Loratadine groups. Post-treatment, immunopharmacological parameters were assessed, and skin tissue was collected for histopathological analysis, mast cell quantification, and immunohistochemistry to evaluate the impact on immune cells and molecules. Serum levels of inflammatory cytokines (TNF-α, IL-6) were quantified using ELISA kits. In vitro, the human mast cell line LAD2 was pretreated with key active components of DGYZ (Quercetin and Paeoniflorin) at different concentrations before mast cell degranulation was induced. Degranulation markers (β-HEX, HIS) and the expression of proteins in immune-related signaling pathways (PI3K-Akt, TLR4) were then measured. Results A total of 38 active components were identified in DGYZ. In vivo, DGYZ inhibited mast cell degranulation, blue spot reactions, and skin damage in mice. It also decreased the levels of inflammatory cytokines (TNF-α, IL-6) and suppressed the activation of associated signaling pathways. In vitro, both Quercetin and Paeoniflorin reduced mast cell degranulation and the activation of TLR4 and PI3K-Akt pathways. Conclusion This study, employing UPLC-Q-TOF–MS and both in vivo and in vitro experiments, provides a comprehensive analysis of the mechanism of DGYZ in CU. The findings indicate that DGYZ exerts therapeutic effects in CU by modulating immune responses. This research lays the foundation for a deeper understanding of its immunopharmacological mechanisms, potentially aiding the development of novel drugs and therapeutic strategies for CU management. Graphical Abstract